Public plazas - the case of João Menna Barreto Plaza - Santa Maria - RS - Brasil - Landscape project methods applied to the discipline of Landscape Architecture II - Limberger, Lucienne Rossi Lopes; Pippi, Luis Guilherme A.; Lazarotto, Gerusa (Paisagem e Ambiente, 2007)
This paper aims to point out methodological procedures used in the discipline Landscape Architecture Project II, given in the 6th semester of the course of architecture and urbanism of the Federal University of Santa Maria. The methodology utilized, based on the objectives of the discipline, which are to understand and apply the intervening variables in the activity of projecting and intervening in the natural and constructed landscape in the contemplation of spaces for squares and walkways, endeavored to underline the importance of open public spaces in the city, which are fundamental for the quality of urban life. The discipline deals with all the basic stages of the landscape project process, while complementing with other exercises that allow the students’ awakening to the concepts of sensibility, responsibility, a sense of community and solidarity as to the urban landscape. All of these concepts should always be developed in the disciplines of academic formation in courses of architecture and urbanism. The stages give the students the opportunity to pass through all the project stages, from the initial stage of awkwardness with the theme to its maturation, allowing for an absorption of all possible information available, considering the square as a live organism in interaction with the city. This awakening to public spaces in the city is fundamental in the formation of architects and urban designers and, as academics, allows an integration with the community. Thus, the students developed surveys, assessments and analyses, considering necessities and developing the studies and the detailing necessary for the elaboration of a final project. The final project was presented to the community in an exposition, demonstrating our role in relation urban landscape of the city.